Official intervention in the forward exchange market: some recent experiences - BLOOMFIELD, A.I. (PSL Quarterly Review, 2014)
In recent years monetary authorities have shown an increased willingness to operate in the forward exchange market as a means of influencing the international flow of short-term funds in desired directions and as a substitute for or supplement to interest-rate changes or other instruments of policy. Recent forward exchange policy provides examples of a number of techniques undertaken in differing circumstances and with differing underlying objectives in mind. However, although the theoretical literature on forward exchange policy continues to grow, almost no attempt has yet been made to assemble and analyse the growing body of information available on the official forward operations of the past five years. The present article employs the available information in order to make a comparative survey of official intervention in the forward market since the restoration of convertibility. JEL: E52, F31